Ціннісна поведінкова модель шляхтича за Литовським статутом 1529 р. - Бондарук, Т.І. (Альманах права, 2012)
Розглядається сукупність ціннісно-правових уявлень шляхти у Великому князівстві Литовському, їх філософсько-правове підгрунття та закріплення у Литовському статуті 1529 року. Расматривается совокупность ценностно-правових представлений шляхты Великого княжества Литовского, их философско-правовое основание и закрепление в Литовском статуте 1529 года. The article is dedicated to the process of compiling values and behavior imaginations of gentry in the Lithuanian Statute as a result of synthesis of the corresponding polish noble — gentry social practices, putting in an order them by making sufficiently precise legal structures. The structure is needed for characteristics as an element of legal culture which forms legal life of medieval man. As a result it is determined one of the essential components of the legal traditions of Ukraine. The article gives the philosophical and religious background to the approach for finding out the relevant social behavioral strategies. In the opposite is the existence of Byzantine Christian philosophy which may be determined by the following criteria: native culture, dividing of individual, personal and collective goods, right and morality, the law and the right etc. The article underline that in medieval epoch did not exist contemporary liberal distinction between law and morality. The moral laws were understood as postulated law: the individual was mostly determined and formed by the certain roles that tied him to the community. The article gives the analyzes of the «honor» and «fame» concept as the highest value of noble status. It gives the philosophical orientation in finding the truth and showing these factors as ones which fix the unconditional and conditional valuable models in Lithuanian Statute 1529. It is emphasis the variability ratings of «good» and evil (sin)» depending on the subject. Due to the necessity to create similar standards, the position of the lawmakers regarding the liability for undue behavior is considered. It was presumed that the main aim of punishment was to provide unavoidability of punishment, execution, intimidation. The biggest threat was recognized as deprivation of honor. There was a sample of special case on avoiding the punishment (art.29, Ch. 7). It is recognized that if the laws quite contains in valuable model, it certainly strengthened its authority. It was announced that gentry keeps strict commitment of «law» as a guarantee of entry and status while there were several cases where gentry try to neglect it. The valuable behavior model of gentry was formed through an idea of honor as a form of identity by belonging to the noble gentry status of «Christianization» and attempted to fix those legislation imperatives.